Model investigations of Strouhal number of iced cable of cable-stayed bridge - Górski, Piotr; Pospišil, Stanislav; Kuznetsov, Sergej; Tatara, Marcin; Marušić, Ante (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The paper presents the method and results of wind tunnel investigations of Strouhal number of stationary iced cable model of cable-stayed bridge. The investigations were performed in a Climatic Wind Tunnel Laboratory of the Czech Academy of Sciences in Telc. The experimental icing of the inclined cable model in the climatic chamber of the laboratory was made. The shape of the iced model was registered by a numerical photogrammetry method. For the aerodynamic tunnel investigations, the new iced cable model was made by using 3D printing method. The Strouhal number was determined within the range of the Reynolds number between 28·103 and 122·103, on the basis of the dominant vortex shedding frequency measured in the flow behind the model.